Assessment Of Knowledge, Attitude, And Practices Of Consumers Vis-À-Vis Functional Foods ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2023)
Background: Functional foods can be defined as foods, which beneficially affect one or more target functions in the  body, beyond adequate nutritional effect, in a way that is relevant to either an improved state of health and wellbeing  and/or reduction in risk of disease. Objective: To assess the Knowledge, Attitude, and Practices (KAP) of consumers  for functional foods. Methodology: A descriptive cross sectional design was adopted for the study which was conducted  in New Delhi. Non probability sampling method was adopted for sample (n= 101) of adult consumers in age range of  20-59 were studied in two age categories, adults (20-39 years) and middle adults (40-59 years). Knowledge, Attitude  and Practice questionnaire was developed with regard to awareness regarding functional food. Data was analyzed on  the basis of age range of subjects by frequency, percentage, mean, standard deviation, z score and correlation. Results: The mean ± S.D. of knowledge scores for adult category was found to be 6.18 ± 2.49 and for middle age adults it was  5.53 ± 1.85. Attitude score of adults was 19.59 ± 2.56 and for middle adults it was 20.07 ± 1.91. The practice score  was 3.79 ± 1.57 for adults and for middle adults it was 4.16 ± 1.13. A significant positive correlation was seen to exist  between the knowledge and attitude, attitude and practice scores of both age categories, for knowledge and practice,  positive correlation was found to exist for adults. Conclusion: The results verified that awareness of functional foods  is associated with greater knowledge about them, more favourable attitudes towards them, along with their increased  consumption.
Keywords: Functional Foods; Knowledge; Attitude; Practice; Awareness; Consumer; Health Benefits